A longitudinal study of cognitive factors influencing start-up behaviors and success at venture creation - Gatewood, Elizabeth J.; Shaver, Kelly G.; Gartner, William B. (Journal of Business Venturing, 1995)
The purpose of this study was to explore whether certain cognitive factors of potential entrepreneurs (as measured by a personal efficacy scale and the kinds of reasons people offer for their decision to undertake efforts to start a business) can be used to predict their subsequent persistence in business start-up activities and in new venture creation success. Two hypotheses were tested: 1.H1: Potential entrepreneurs who offer internal and stable explanations for their plans for getting into business (e.g., “I have always wanted to own my own business”) should be more likely to persist in actions that lead to successfully starting a business.2.H2: Potential entrepreneurs with high personal efficacy scores should be more likely to persist in actions that lead to successfully starting a business. The beginning pool of subjects for this research consisted of 142 consecutive preventure clients (47 women, 95 men) of a Small Business Development Center between October 1990 and February 1991. As part of their initial consultation, these individuals were asked to explain their decision to enter business. These responses were coded on the basis of a detailed procedure derived from the attributional model (Weiner 1985). Potential entrepreneurs also responded to a locus-of-control questionnaire: Paulhus (1983) Spheres of Control Scale. In February 1992, all 142 people were sent a follow-up questionnaire designed to assess the extent of their new venture development activity in the intervening year. Responses from 85 individuals were available for this analysis. The follow-up questionnaire listed 29 separate activities involved in starting a business. These activities were grouped into five major categories: gathering market information, estimating potential profits, finishing the groundwork for the company, structuring the company, and setting up business operations. The measure of success at getting into business was operationalized by the question: “Have you completed the first sale (defined as having delivered the product or service and collected the payment from your customer)?” An analysis of the results found that HI (internal/stable attributions, e.g., “I have always wanted to be my own boss”) was supported for female potential entrepreneurs, whereas external/stable attributions (e.g., “I had identified a market need”) were significant for male potential entrepreneurs. SIC code classifications revealed no significant differences in the sorts of businesses being contemplated by women and men. H2 (personal efficacy) was not supported. Those activities that focused on setting up business operations (e.g., purchasing materials, hiring employees, producing the product/service, distributing the product) distinguished potential entrepreneurs who had started businesses from those who had not. We believe that one of the important features of this research is the use of a longitudinal research design. By measuring attributions before these potential entrepreneurs had started (or not started) their businesses, we can make stronger claims for a causal relationship between initial attributions and each individual's subsequent success or failure in business start-up. Given all of the events and activities that occur between an individual's attributions for getting into business and the actual start-up, the attributional findings about male and female potential entrepreneurs have important implications for future research and practice. Men and women do have different reasons for getting into business that appear to be significant indicators of their future ability to start a business successfully. We believe that the development of measures focusing on details of the attributional model (i.e., perceptions of skills, abilities, the difficulty of the task, luck, and the value of the opportunity) will likely lead to a more comprehensive and accurate conception of the factors that influence entrepreneurial persistence. We offer some suggestions for how the use of an attributional model might influence the selection, counseling, and training of potential entrepreneurs.